Growth assessment and weight management in paediatric neuromuscular clinics: a cross-sectional survey across Canada. Issue 21 (9th October 2021) - McPherson, Amy C.; Amin, Reshma; McAdam, Laura; Kalnins, Daina; Lui, Toni
Abstract: Purpose: To identify current practices related to the assessment, monitoring and discussion of bodyweight, growth and obesity in neuromuscular clinics for children with Duchenne muscular dystrophy (DMD). Methods: A cross-sectional, online survey was distributed using snowball sampling to healthcare providers working with children with DMD across Canadian neuromuscular clinics. Summary and descriptive statistics were calculated. Content analysis was performed on open text responses. Results: Thirty-seven responses were received, representing a range of healthcare disciplines. Height and weight were routinely assessed by 32/37 (87%) respondents, although only 21/37 (57%) responses reported having a clinic standard for measuring height and 23/37 (62%) for weight. While 32/36 (89%) reported discussing weight during consultations, only 13/37 (35%) felt confident doing so. Dietitians were considered the most appropriate person to discuss and manage weight with children and families, although only 17/37 (46%) reported having a dietitian involved in their clinic. Conclusions: Neuromuscular clinics could benefit from implementing consistent and recommended growth assessment practices. The development of evidence-based tools, training and protocols tailored to Duchenne muscular dystrophy should be a priority. IMPLICATIONS FOR REHABILITATION: Growth and weight monitoring approaches vary within and between neuromuscular clinics. Additional training on discussing and managing weight are warranted across disciplines. Advocacy is required to ensure access to dietetic expertise within neuromuscular clinics.